Contriving an Opinion of Cause of Death in Autopsies - Anu Sasidharan1 , Nadia M. Al-Kandary2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Contriving an opinion of cause of death is something that requires a good expertise in the subject knowledgeand the right set of discriminative skills. The immediate and basic causes of death, circumstances surroundingthe death, and the investigation findings of police officers are all the necessary prerequisites to be gathered,before formulating an opinion. Decisions on the cause of death most often de facto will decide the mannerof death.A forensic pathologist can give causes of death in a logical sequential manner. Hume’s and Mill’s philosophyis something to be always borne in the mind of a forensic pathologist. Istanbul Protocol is the only literaturementioning as to how to opine an effect, with respect to the causes or circumstances that led to the effect.This can be extrapolated to have five different compartmentalised categories of opinions. Unless there iscertain uniformity in opining, the more are the chances of confusion among our fraternity and the judiciary